The Application of Jigsaw Cooperative Learning Model towards the Improvement of Students' Critical Thinking Ability in Public Senior High School 15 Banda Aceh, Indonesia - Ismail Ismail (BIRCU, 2020)
The purpose of this study is to analyze the application of Jigsaw Cooperative Learning model towards the improvement of students' critical thinking ability in Public Senior High School 15 Banda Aceh, Indonesia. The results showed that the students' ability in answering questions before learning using the jigsaw learning model was still in the low category or the initial research proved that most students were not able to answer the questions well, so the researchers took the next action, namely learning by using a jigsaw type cooperative learning model , the results of information obtained from learning conducted before the implementation of the study, while the information from the control class is low category consisting of 3 students, while the medium category is 9 students, and while the high category there are 7 students while the information in the experimental class is low category consists of 1 student, 11 students and a high category of 8 students, which can be concluded that there are differences in students' critical thinking outcomes with the use of a jigsaw type cooperative learning model.